(3GdETQGa Ydi HYV ef HaGS ef eTGgjQ GdCTQGas - (3GdWGdH GHf GdMGL , eMeO GdWGdH Hf MeOhf Hf YHO GdQMef GdMGL GdSdej GdHNGQj GdaGSj,J (B1273 (3g` s
(3ChdgG (B:s
(3hHYO agPg ahGFO TQjaI hYhGFO efjaI JVefJ GdETQGa Ydi HYV ef HaGS ef eTGgjQ GdCTQGa s
(3BNQgG (B:s
(3bGd eajOI gfG fLRHfG Gdbhd aj gPg GdfHPI GdjSjQI bhd GdYLGdI GdeNJdSI hUdi Gddg Ydi SjOfG hfHjfG hehdGfG eMeO hGab GdaQGZ ef JHjjVg VMhg jhe GdSHJ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B124s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B171 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B95s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B32 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs